Effect of Crop Age and Seed Hardening on Seed Germination in BuffeI Grass - Rajora, M p; Yadav, M S; Sharma, S K (Annals of Arid Zone, 2016)
Effect of crop age, viz., cstablishment year, I-year and 2-year-old crops and hydration treatment, viz., untreated (control), hydration for 16 to 18 h (1-1-0). cold hydration (72 h) at lOoC (cold I-I-D), hydration with 100 ppm GA3 for 16 to 18 h (GA3 !-I-D), and hydration for ]6-18 h followed by dry dressing with thiram @ 0.25% (!-I-O-T) on seed germination was studied in butTel grass (Cenchrus ciliaris Linn.). The treated seeds were dried at room temperature below 25Â°C. The crop ages, hydration treatments and their interaction had significant effect on seed germination. The seeds harvested from the establishment-year-erop gave 37.0 and 47.1 % higher germination than the seeds of I-year and 2-year-old crops, respectively. The seed germination recorded with cold H-O and GA3 H-O was signiji antly higher than rest of the hydration treatments. These treatments had 21.82 and 21.32% higher seed germination than control (50.42%).